2020
DOI: 10.1371/journal.ppat.1008354
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte metabolic reprogramming promotes pro-inflammatory activity and Staphylococcus aureus biofilm clearance

Abstract: Biofilm-associated prosthetic joint infections (PJIs) cause significant morbidity due to their recalcitrance to immune-mediated clearance and antibiotics, with Staphylococcus aureus (S. aureus) among the most prevalent pathogens. We previously demonstrated that S. aureus biofilm-associated monocytes are polarized to an anti-inflammatory phenotype and the adoptive transfer of pro-inflammatory macrophages attenuated biofilm burden, highlighting the critical role of monocyte/macrophage inflammatory status in dict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 85 publications
3
68
0
Order By: Relevance
“…A critical role for S. aureus atpA in attenuating the host immune response in vivo was demonstrated by the finding that Δ atpA elicited heightened proinflammatory mediator production in a mouse model of S. aureus PJI. This coincided with a significant reduction in MDSCs concomitant with increased monocyte and MΦ recruitment, a relationship that our prior studies have established coincides with biofilm clearance ( 18 , 20 , 22 , 27 , 42 ).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…A critical role for S. aureus atpA in attenuating the host immune response in vivo was demonstrated by the finding that Δ atpA elicited heightened proinflammatory mediator production in a mouse model of S. aureus PJI. This coincided with a significant reduction in MDSCs concomitant with increased monocyte and MΦ recruitment, a relationship that our prior studies have established coincides with biofilm clearance ( 18 , 20 , 22 , 27 , 42 ).…”
Section: Discussionsupporting
confidence: 75%
“…aureus ATP synthase attenuates MDSC and M⌽ inflammatory responses to biofilm. Previous studies from our laboratory have demonstrated that S. aureus biofilm skews leukocytes to an anti-inflammatory state, which promotes bacterial persistence (18,19,27). To determine if S. aureus ATP synthase-dependent pathways play a role in this process, primary bone marrow-derived MDSCs and M⌽s were cocultured with ΔatpA biofilm to quantify cytokine production.…”
Section: Resultsmentioning
confidence: 99%
“…Monocytes that are associated with biofilm infections are polarized toward an anti-inflammatory state (Le et al, 2018;Yamada et al, 2020). Directed uptake by monocytes of nanoparticles coated with the mitochondrial oxidative phosphate inhibitor oligomycin reprogrammed metabolism toward pro-inflammatory glycolysis (Yamada et al, 2020). These macrophages reduced biofilm density in vitro and in vivo in a mouse model of biomaterial-associated bone infection.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic preferences of the monocytes recruited during the immune response to S. aureus also influence the outcome of the infection [16]. In contrast to the S. aureus isolates from the skin that induce host glycolysis and inflammation, the strains from prosthetic joint infections, which are prolific biofilm formers, promote oxidative phosphorylation in the recruited macrophage-monocyte population [16]. These immune cells have anti-inflammatory properties including IL-10 and arginase production.…”
Section: Host Metabolism Promotes Infectionmentioning
confidence: 99%
“…The simultaneous changes in host and staphylococcal metabolism during S. aureus infection have a major impact on the clearance of infection [ 6 , 9 , 15 , 16 ]. In the pathogenesis of pneumonia, aspirated bacteria must rapidly adjust their metabolic activity to consume nutrients now available in the airway that differ from those in the sites of initial colonization in the nares.…”
Section: Introductionmentioning
confidence: 99%